SC10 Design, development and delivery of a distributed in-situ simulation programme in a tertiary-referral teaching hospital. (November 2018) - Bux, Mohammed; McNutt, Andy; Kamalanathan, Kajan; Freshwater-Turner, Daniel
Abstract : Background: Simulation-Based Education (SBE) is effective and can be used to address deficiencies in knowledge, skills, attitudes and behaviours, and also to test systems for latent errors. This contributes to improvements in patient safety. In-situ simulation maximises authenticity and context of the learning experience and improves the ability to train interprofessionally. Summary of programme: Since 2012, University Hospitals Bristol NHS Foundation Trust (UHBT) has developed a programme of SBE with an in-situ focus. This means that staff do not need to be released from clinical work for extended periods, and the programme is delivered with a minimal investment in resource. Initially based in three areas (Emergency Medicine, Intensive Care and Medical Admissions Unit) it has expanded over time, and now reaches 23 clinical areas across all divisions of the Trust at least monthly. A cascade model of faculty development has been adopted, where the programme faculty initially deliver teaching to an area but then identify staff members from that area to take over their local SBE activity. Faculty training and mentoring is provided during this period to facilitate this. Activity in the programme is recorded, with feedback gathered for all teaching interventions. Teaching is focused on issues of relevance, with both Trust-wide and local priorities feeding into the content. Summary of results: Since April 2016, 1614 learner interactions were recorded within the programme. 78%–100% of learners either agree or strongly agree that the teaching is enjoyable, delivered at an appropriate level and relevant to their practice. Self-reported confidence in assessing and managing acutely unwell patients increased by 32%–35%. Numerous systems errors have been identified in clinical areas through the activity of the programme, and steps have been taken to minimise the risks to patients as a result. Discussion, conclusions and recommendations: In developing and delivering this programme, we have shown that in-situ simulation is a cost-effective way of delivering teaching to large numbers of clinical staff without the need to release them from clinical duties for prolonged periods. Despite acute pressures within our busy hospital, we have been able to deliver effective teaching reliably and demonstrate patient safety benefits. Our distributed model of faculty development has allowed us to develop the programme while maintaining control over quality, allowing us to ensure that the teaching in each area is directly relevant to each clinical area and in keeping with trust-wide priorities